Mental health intervention program during the COVID-19 for Mexican adults - Briceño Rodríguez, Mariel B; Gutiérrez-García, Raúl A (Gaceta Médica de Caracas, 2022)
Introduction: The current pandemic caused by COVID-19 is a public health emergency with serious economic, educational, and social consequences. Its consequences are not only manifested in physical aspects, it is increasingly evident that this crisis is producing alterations in the mental health of the population, which is why it is of utmost importance to analyze the repercussions that COVID-19 could cause on mental health and the measures for its prevention and control, as well as the strategies to favor it.